GLOBAL IMPACTS OF THE PANDEMIC CRISIS ON THE MARKET OF TRANSPORT SERVICES - RYBCHUK, Anatoly; ZHURBA, Igor; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Further expansion and deepening of globalization processes largely depends on the efficiency of functioning of such an important infrastructure element as transport. For several centuries, transport has been the leading link that connects national economies and their business entities. Transportation is a key area of the global economy that fulfills society’s vital need to move passengers, labor, and goods. It is transport that creates the basis for effective foreign and domestic trade, passenger and cargo transportation. The expansion of the scale of world trade, associated with the deepening of the international division of labor, led to the rapid growth of the transport services market, which was temporarily affected by the global pandemic. The article examines the peculiarities of the functioning of the transport services market in the pre-crisis period and in the global pandemic. The impact of the pandemic crisis on all segments of the global passenger and freight industry is analyzed. It is established that a number of peculiarities can be traced in the functioning of structural elements of the transport market in the conditions of COVID-19: secondly, rail transport services have been significantly reduced due to severe quarantine restrictions, reduced train traffic and a global decline in production; third, declining trade and supply chain disruptions have led to restrictions on road transport; fourth; the demand for passenger air transportation decreased the most during the analyzed period; fifth, the global market for pipeline transport services has been slightly affected by co-constraints and is showing strong growth. The gradual recovery of all segments of the global transport services market has been confirmed.